(untitled) (Journal of Patan Academy of Health Sciences, 2024)
The introduction of a scientific journal article is the first section of the manuscript a reader goes through. The introduction establishes the context for the research, highlights the gap in knowledge that the study aims to address, and articulates the objectives of the topic under study. The way it is presented can be detrimental for the reader in making a decision whether to go to the next section of the article or to discard it entirely.1 A well-crafted introduction not only grabs the reader’s attention but also sets the tone for the entire paper. Writing a good introduction takes a thorough understanding of the topic, and also the essence of how the study is going to answer the research question. Many authors, especially newbees, make some common mistakes when drafting this essential section. Understanding these pitfalls and avoiding them can significantly improve the clarity and impact of a manuscript.